Safety and efficacy of an iBTA-induced autologous Biotube vascular graft and its preparation device BTM1 in below-the-knee bypass surgery for chronic limb threatening ischemia: A protocol for an open-label, single-arm, multicenter clinical trial - Takashi Shuto; Ryuji Higashita; Hidenori Sako; Fumie Abe; Nozomi Yabuuchi; Tadashi Umeno; Kazuki Mori; Takayuki Kawashima; Yumiko Nakashima; Yasuhide Nakayama; Shinji Miyamoto (PLoS ONE, 2025)
Purpose Chronic limb-threatening ischemia (CLTI) increases the risk of lower limb amputation if revascularization is not performed. The use of autologous venous conduits is the only option for patients requiring below-the-knee bypass surgery, but it is limited by a lack of usable veins. The Biotube Maker (BTM1), based on in-Body Tissue Architecture (iBTA) technology, is a mold for the in vivo production of the Biotube® regenerative artificial vascular grafts. This clinical trial is designed to evaluate the safety and efficacy of subcutaneous embedding of the BTM1 for Biotube preparation and arterial bypass surgery using Biotube. Methods Patients with CLTI who lack suitable veins for bypass surgery will be enrolled. This exploratory, investigator-initiated clinical trial will include 12 subjects. The primary endpoint is successful formation of an implantable Biotube following subcutaneous embedding of the BTM1. Secondary endpoints include intraoperative usability, patency and biocompatibility of the Biotube, wound healing, relief of rest pain, limb salvage, and procedure-related mortality, assessed up to 12 weeks after surgery. These outcomes are expected to provide essential feasibility and safety data to guide future pivotal studies. Discussion This study may offer a new treatment option for CLTI patients who otherwise face major amputation. If feasibility and safety are confirmed, the findings will support planning of a pivotal trial aimed at regulatory approval. Trial registration jRCT2072220062. Registered on October 19, 2022.